Synthesis, thermionic emission and magnetic properties of （NdxGdl-x）B6 - 包黎红 张久兴 周身林 持古斯 (中国物理：英文版, 2011)
Polycrystalline rare-earth hexaborides （NdxGdl-x）B6 （x = 0, 0.2, 0.6, 0.8, 1） were prepared by the reactive spark plasma sintering （SPS） method using mixed powder of GdH2, NdH2 and B. The effects of Nd doping on the crystal structure, the grain orientation, the thermionie emission and the magnetic properties of the hexaboride were investigated by X-ray diffraction, electron backscattered diffraction and magnetic measurements. It is found that all the samples sintered by the SPS method exhibit high densities （〉95%） and high values of Vickers hardness （2319 kg/mm2）. The values are much higher than those obtained in the traditional method. With the increase of Nd content,the thermionic emission current density increases from 11 to 16.30 A/cm2 and the magnetic phase transition temperature increases from 5.85 to 7.95 K. Thus, the SPS technique is a suitable method to synthesize the dense rare-earth hexaborides with excellent properties.